2015
DOI: 10.1093/ofid/ofv012
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant Susceptibility to Malaria During the First Year of Life in South Western Cameroon

Abstract: Background. Falciparum malaria is an important pediatric infectious disease that frequently affects pregnant women and alters infant morbidity. However, the impact of some prenatal and perinatal risk factors such as season and intermittent preventive treatment during pregnancy (IPTp) on neonatal susceptibility has not been fully elucidated.Methods. A cohort of 415 infants born to women who were positive and negative for malaria was monitored in a longitudinal study in Southwestern Cameroon. The clinical and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
(67 reference statements)
0
34
0
Order By: Relevance
“…These studies detected more infections in the rainy than in the dry season but unexpectedly higher MSP diversity in the dry season than in the rainy season [41] and lowered MOI in the rainy season with higher polyclonal infections in the dry seasons [42] . In South-Western Cameroon where malaria transmission is perennial, a similar paradox was observed where infants born during the wet season were more susceptible to malaria infection while children born in the dry season were protected [43]. MOIs for residents of Kintampo coincided with the lowest entomological inoculation rates (EIR), at the end of the dry season, while the lowest MOIs coincided with the highest EIR at the end of the wet season [4, 35].…”
Section: Discussionmentioning
confidence: 97%
“…These studies detected more infections in the rainy than in the dry season but unexpectedly higher MSP diversity in the dry season than in the rainy season [41] and lowered MOI in the rainy season with higher polyclonal infections in the dry seasons [42] . In South-Western Cameroon where malaria transmission is perennial, a similar paradox was observed where infants born during the wet season were more susceptible to malaria infection while children born in the dry season were protected [43]. MOIs for residents of Kintampo coincided with the lowest entomological inoculation rates (EIR), at the end of the dry season, while the lowest MOIs coincided with the highest EIR at the end of the wet season [4, 35].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, one recent study also found that infants were specifically at increased risk of parasites that carried a matching glurp allele as those that infected their mothers’ placentas . However, these associations are not universal, as in additional studies conducted in Ghana, Cameroon and Benin, PM was not associated with an increased risk of malaria infection or clinical malaria in infants (Table ) …”
Section: Maternal Malaria Predicts An Increased Risk Of Malaria Durinmentioning
confidence: 98%
“…124 Consistent with this model, several studies have reported that infants born to women with PM are themselves at higher risk of malaria during early life. [8][9][10][11]125,126 However, this association has not been observed in all cohorts, [127][128][129] and indeed one study found that infants of primagravidas with PM actually have a lower risk of parasitemia during infancy. 7 A parsimonious explanation for the repeated observation of higher infant malaria risk following in utero exposure is that these studies are confounded by variability in exposure.…”
Section: Doe S In Utero Anti G En E Xp Osure Impac T the De Velopmementioning
confidence: 99%